(untitled) (An Naba, 2023)
Human resources are the main element in an organization, including in the world of Islamic boarding schools. Therefore, human resources need to be developed so that the quality of human resources continues to improve for the sustainability of the institution. This article was written with the aim of knowing the process of implementing human resource development in Islamic boarding schools and the importance of human resource development for Islamic boarding schools. The approach in this study was qualitative with a case study design, namely at the Al Kamal Blitar Integrated Islamic Boarding School, data collection was carried out by interview, observation and documentation techniques. Based on data analysis, several results were found, including: 1) Development of human resources at the Foreign Language Development Institute was carried out by coaching and training language tutors who were given directly by the chairperson or invited competent speakers, to oversee the course of language classes, a WhatsApp group was provided which served as teaching journal. 2) This development is important to do to improve the quality of tutors who will teach languages to students and to preserve foreign languages as an institutional identity program that can show a positive image of Islamic boarding schools through the output they produce.